TINJAUAN HUKUM ISLAM TERHADAP IMPLEMENTASI AKAD MUSHARAKAH MUTANAQISAH SEBAGAI SOLUSI AKAD PEMBIAYAAN KREDIT PEMILIKAN RUMAH PADA BANK SYARI’AH - M. Taufiqurrosyidin Abdillah (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2015)
Musharakah mutanaqisah contract is a form of contract solutions murabahahÂ formerly used as a mortgage financing agreement with Bank Muamalat Indonesia.The implementation of the contract musharakah mutanaqisah on mortgage financing product is a form of cooperation partnerships undertaken by the bank and the customer in the housing where the bank contributes funds to customers based on mutual agreement. Whereas ijarah contract is an aggrement which is obligated to client to pay a number of rent payment which was given by side of bank as the service because it has become the object of utilizing home mortgage financing is accompanied by the transfer of ownership of the house at the end of the full payment. Thus, the study of Islamic law in the implementation of the contract musharakah mutanaqisahÂ has met its validity, because its pillars and conditions have been met.